How social entrepreneurs learn new skills? The role of social economy support centres in supporting know-how development - Wronka-Pośpiech, M. (Видавництво Львівської політехніки, 2021)
The modern business model means that, regardless whether for-profit or non-profit, an organization should have both the willingness and the ability to learn and develop. Nowadays social enterprise has emerged as a key factor in efforts to address the many complex issues facing the world today. Its focus on providing a benefit to society as a whole rather than just the owners of the enterprise make it ideal for addressing the global concerns of the environment, healthcare, education, economic growth, and poverty alleviation. This article demonstrates specific examples on how Social Economy Support Centres create policy programmes for social enterprises and support their legal, financial and know-how development.
Keywords: social enterprise; social entrepreneurship; entrepreneurial support; Z18; P13; P23; 338.246.02